Pentingnya Kecerdasan Emosional Terhadap Kepemimpinan Hamba Tuhan Dalam Pengambilan Keputusan Berdasarkan 1 Raja-Raja 3:16-28 - Setiawan, David Eko; Tasane, Rosanti (Jurnal Kala Nea, 2024)
Spiritual leadership requires more than just theological knowledge or preaching skills. Emotional intelligence is one of the essential elements of leadership, enabling leaders to recognize, manage, and utilize emotions effectively. In the context of church leadership, this ability becomes crucial in dealing with pressure, conflicts, and wise decision-making. This study examines the relevance of emotional intelligence in church leadership by referring to the story of King Solomon in 1 Kings 3:1-28. This narrative highlights how wisdom and emotional sensitivity were employed to resolve conflicts fairly. The analysis connects modern emotional intelligence with biblical principles, demonstrating that emotional intelligence significantly contributes to decision-making based on emotional control, empathy, and effective communication. This research aims to enrich the understanding of church leadership and enhance the quality of leadership among God’s servants.